A review study on medicinal plants affecting amnesia through cholinergic system - Baradaran Azar; Rabiei Zahra; Rafieian Mortaza; Shirzad Hedayatollah (Shahrekord University of Medical Sciences, 2012)
Neurotransmitter modification is an important method for the treatment of memory loss or amnesia. Cholinomimetic drugs, particularly, acetylcholine esterase inhibitors are the mainstream in pharmacotherapy of amnesia. Donepezil, tacrine, galantamine, and rivastigmine are cholinesterase inhibitors which are widely used in the treatment of amnesia, however, their therapeutic effects are not significant. Therefore, other possibilities including herbal medicine sources have been considered for memory loss therapy. There are some Medicinal plants with cholinomimetic property which mostly possess antioxidant activity, too. These plants may not only ameliorate amnesia but also can be a good source for drug discovery. In this paper other than introducing the medicinal plants and their components affective on cholinergic system and effective on memory loss, their probable advantages over synthetic drugs are discussed.